Distribution mechanism of disperse dyes with similar substituents in a waterless dyeing system based on molecular dynamic simulation. (June 2022) - Zhang, Hongjuan; Yu, Shunjie; Guo, Jing; Hu, Fan; Pei, Liujun; Liang, Shuaitong; Yang, Qun; Wang, Jiping
Abstract: In this paper, starting from the dye molecular structure activity relationship, the effect of substituents on the coloration process, such as dissolution, adsorption and diffusion behaviors, was investigated by molecular dynamics simulations in a waterless dyeing (D5) system. Related dyeing experiment test were performed to verify the accuracy of the simulation results. The results showed that the diffusion coefficient of disperse dyes decreased gradually due to an introduction of one ortho-substituent cyano group compared with unsubstituted dyes. Meanwhile, using the substituent N-cyanoethyl group instead of N-ethyl group in coupling component further decreased the diffusion coefficient, which was attributed to an increase of aggregation capacity. Simultaneously, the solubility of disperse dyes containing bis N-cyanoethyl groups in D5 media also decreased obviously due to the low dye-D5 interaction energy, which was consistent with their aggregation behavior. Additionally, the growing strong interaction energy between dye molecules and polyester fibers due to an introduction of cyano group or N-cyanoethyl group contributed to increasing the adsorption efficiency and dyeing uptake. It will be an effective and labor-saving method to select and develop the special disperse dyes for the sustainable D5 dyeing system. Graphical abstract: Image 1 Highlights: Distribution mechanism of disperse dyes was investigated based on molecular dynamic simulation. The aggregation of disperse dye containing cyano, especially bis N-cyanoethyl groups, increased compared with unsubstituted dye. The growing interaction energy between dye and polyester fibers contributed to increasing dyeing uptake.